Feira da agricultura familiar nas universidades públicas do Brasil: estudo de caso da feira da agricultura familiar da UFOPA. - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
This study investigates family farming fairs held within Brazilian federal public universities, focusing on the case of the Family Farming Fair of the Federal University of Western Pará (UFOPA), located in Santarém-PA. The main objective is to understand the scope and diversity of formats of family farming/artisanal fairs held at federal public universities in Brazil, with particular attention to the UFOPA Family Farming Fair (FAF). Based on a qualitative approach, the research involved bibliographic review, documentary analysis, and a case study, in addition to the application of a questionnaire sent to federal higher education institutions. The results show that these fairs serve as spaces for integration between the academic community and local producers, promoting income generation, social inclusion, the appreciation of sustainable practices, and, especially, innovation. At UFOPA, innovative actions guided by solidarity economy stand out, such as the Ecobox project, solidarity and thematic fairs, and logistical support for exchange activities. These initiatives have contributed to the empowerment and visibility of different social groups, such as women farmers and Indigenous peoples. The analysis highlights the importance of these fairs as institutional mechanisms for strengthening family farming and fostering closer ties between the university and its surrounding territory.
Keywords: Feira da Agricultura Familiar da UFOPA; Feiras nas Universidades; Economia Solidária; IECOSOL; CNPQ:: CIÊNCIAS SOCIAIS APLICADAS